Household Carbon Footprint: How Does Age Structure Affect Emissions? - Meli Nopiyani; Djoni Hartono (Universitas Negeri Semarang, 2026)
This study analyzes the influence of household age structure on carbon emissions in Indonesia using a quantitative approach based on micro-level survey data. Employing an Ordinary Least Squares (OLS) regression model, it introduces the average age of household members and its squared term to capture potential non-linear effects. The results reveal a non-linear, inverted U-shaped relationship between household age and per capita carbon emissions. The turning point occurs at approximately 36 years, suggesting that households with members around this average age tend to have the highest emissions, which then decline as the average age increases further. This finding aligns with the Life-Cycle Hypothesis, which posits that households in their productive years exhibit more energy-intensive consumption patterns. In addition, the study explores variations in emissions across different household age compositions those dominated by children, adults, and elderly structures. By incorporating these classifications, along with relevant socio-economic and physical household characteristics, the analysis provides deeper insights into how demographic profiles shape energy use and emissions. These findings offer valuable input for developing more targeted and equitable low-carbon policy interventions.